Improving supply security: Guidelines and policy proposals - Gabriel Felbermayr; Eckhard Janeba (Intereconomics, 2024)
Supply security is threatened by technical, business, natural and policy shocks, as well as geopolitical tensions. Is there a rationale for policy intervention? If yes, what are efficient and effective measures that achieve de-risking? This article first explains why private incentives do not generally lead to an optimal diversification of supply sources, and then discusses measures that strengthen protection against and resilience in the face of shocks. Governments should refrain from policies that further disincentivise diversification such as the ex post skimming of excess profits when adverse shocks force the halt of production and should work on framework conditions that facilitate diversification. Importantly, most measures are best taken at the EU level.
Keywords: F13; F51; L5; 330; Foreign trade; Supply chain; Economic security; Außenhandel; Lieferkette; Wirtschaftliche Sicherheit